Real-world first-line serplulimab therapy for advanced esophageal cancer: effectiveness, safety, and clinical implications - Yan, Fei; Zhu, Jingni; Wu, Qibing; Ren, Yuanyuan; Yu, Xinnian; Sun, Zijian; Liu, Yang; Sun, Changjiang; Sun, Yan (Frontiers in Medicine, 2025)
ObjectiveThe phase III ASTRUM-007 trial demonstrated significant clinical benefit in patients with PD-L1-positive esophageal squamous cell carcinoma (ESCC) treated with first-line serplulimab plus chemotherapy. This multicenter, observational cohort study aimed to evaluate the real-world outcomes, and address evidence gaps in broader patient populations.MethodsThis multicenter real-world cohort study collected the data of patients with locally advanced or metastatic esophageal cancer who received first-line serplulimab treatment, regardless of histologic type and PD-L1 expression. The outcomes included real-world progression-free survival (rwPFS), objective response rate (ORR), disease control rate (DCR), overall survival (OS) and safety.ResultsAmong 104 included patients, the median number of serplulimab treatment cycles was four; 10 patients (9.6%) concurrently received targeted therapy, 21 (20.2%) received radiotherapy, and 97 received chemotherapy (93.3%). The confirmed ORR was 40.0% (95% confidence interval [CI]: 29.8–50.9%) and the DCR was 97.8% (95% CI: 92.2–99.7%). With a median follow-up time of 6.8 months, the median rwPFS was 12.00 months (95% CI: 8.87-not reached [NR]). The median OS was not reached (95% CI: 13.27-NR), with a 1-year OS rate of 73.5% (95% CI: 60.4–89.3%). Subgroup analysis showed prolonged median PFS in patients aged ≥65 years than those <65 years (12.00 vs. 6.87 months, p = 0.022). Only two serious adverse events were reported (one hyperkalemia and one decreased white blood cell count).ConclusionThis real-world study supports the effectiveness and safety of serplulimab-based regimens as a first-line treatment for patients with locally advanced or metastatic esophageal cancer, regardless of their diverse characteristics.